Effects of grain sorghum hybrid on finishing pig performance - Goldy, G.; Hines, Robert H.; Goodband, Robert D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two trials were conducted to compare the feeding value of homozygous and heterozygous yellow endosperm grain sorghum and corn for finishing pigs. Homozygous yellow endosperm grain sorghum had no advantage in feeding value over heterozgous yellow endosperm hybrids (P>.05). Finishing hogs fed grain sorghum hybrids did not differ (P>.05) in average daily gain, feed intake, or feed efficiency compared to those fed a corn diet.
Keywords: Swine; Grain sorghum; Finishing pig performance